2020
DOI: 10.3390/microorganisms8101459
|View full text |Cite
|
Sign up to set email alerts
|

Role of Infections in the Pathogenesis of Rheumatoid Arthritis: Focus on Mycobacteria

Abstract: Rheumatoid arthritis (RA) is a systemic inflammatory autoimmune disease characterized by chronic erosive polyarthritis. A complex interaction between a favorable genetic background, and the presence of a specific immune response against a broad-spectrum of environmental factors seems to play a role in determining susceptibility to RA. Among different pathogens, mycobacteria (including Mycobacterium avium subspecies paratuberculosis, MAP), and Epstein–Barr virus (EBV), have extensively been proposed to promote … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 187 publications
(239 reference statements)
2
24
0
1
Order By: Relevance
“…Several studies have indicated that immune-inflammatory responses to Mtb, as well as non-tuberculous mycobacteria (NTM), can drive the pathogenesis of IMIDs and signaling via toll-like receptors (TLRs) plays an important role in this process [ 10 , 11 ]. Cell membrane-associated glycolipids and lipoproteins of Mtb serve as microbe-associated molecular patterns (MAMPs) recognized by the pattern-recognition receptors (PRRs, including TLRs) of innate immune cells [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have indicated that immune-inflammatory responses to Mtb, as well as non-tuberculous mycobacteria (NTM), can drive the pathogenesis of IMIDs and signaling via toll-like receptors (TLRs) plays an important role in this process [ 10 , 11 ]. Cell membrane-associated glycolipids and lipoproteins of Mtb serve as microbe-associated molecular patterns (MAMPs) recognized by the pattern-recognition receptors (PRRs, including TLRs) of innate immune cells [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The pro-inflammatory cytokines produced by these cells, besides orchestrating innate immunity against the invading microbe, can trigger pathogenesis of RA and other IMIDs [ 6 ]. Antigenic constituents of Mtb membrane (MtM) are also potent inducers of adaptive immunity which, in turn, may contribute to the pool of pro-inflammatory cytokines [ 10 , 12 ]. Mtb ‘immunoproteome’ is rich in membrane-associated and secreted proteins [ 13 ] and certain MtM-associated proteins identified by us [ 14 ] and others [ 15 ] were found capable of inducing strong T cell responses in persons with LTBI.…”
Section: Introductionmentioning
confidence: 99%
“…In the same region, nearly 31% of 28,291 humans tested positive for MAP as well [ 81 ]. MAP has also been implicated in the pathogenesis of rheumatoid arthritis – which not uncommonly co-exist and has overlapping features with SS [ 82 ]. More specifically, supporting evidence for the link between mycobacteria and rheumatoid arthritis include the finding of mycobacterial antigens in the joints of rheumatoid arthritis patients and of increased level of anti-mycobacterial antibodies in their sera [ 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have suggested that mucosal surfaces, specifically the periodontium, the gut, and the lungs, might be privileged sites of autoimmunity initiation in RA [ 5 ] ignited by a humoral and cytotoxic immune response against mucosal-associated pathogens [ 6 ]. Accordingly, there is convincing evidence that immunity against mucosal microbial pathogens such as Porphyromonas gingivalis ( P. gingivalis) and Aggregatibacter actinomycetemcomitans ( A. actinomycetecomitans ) may be linked to RA development [ 7 , 8 , 9 , 10 ]. RA-related autoantibodies against these pathogens are stimulated in different ways.…”
Section: Introductionmentioning
confidence: 99%